2015
DOI: 10.6004/jnccn.2015.0178
|View full text |Cite
|
Sign up to set email alerts
|

Independent Prognostic Value of Serum Markers in Diffuse Large B-Cell Lymphoma in the Era of the NCCN-IPI

Abstract: In our cohort, we describe the most promising markers to improve the NCCN-IPI. Anemia and high C-reactive protein levels retain their power in multivariate testing even in the era of the NCCN-IPI. The negative role of high bilirubin levels may be associated as a marker of liver function. Further studies are warranted to incorporate these markers into prognostic models and define their role opposite novel molecular markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…Three studies[2527] were found to be eligible through updated searching. In total, 9 studies [12, 13, 17, 18, 2529] with 2297 patients were included for the meta-analysis. The main characteristics of included studies are demonstrated in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies[2527] were found to be eligible through updated searching. In total, 9 studies [12, 13, 17, 18, 2529] with 2297 patients were included for the meta-analysis. The main characteristics of included studies are demonstrated in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies[12, 13, 17, 18, 2527] were published in English and 2 studies [28, 29] were published in Chinese. Eight studies [12, 13, 17, 18, 2629] investigated the association between NLR and OS and 7 studies [12, 17, 18, 2527, 29] reported a connection between NLR and PFS. All studies obtained a NOS score of ≥7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low serum albumin and low BMI are frequent findings in patients with advanced malignancy, and can be considered as proxy variables for poor performance status and cancer-associated cachexia/anorexia [4,5]. A combination of these variables, such as the ALI, may lead to a more refined outcome prediction as compared to using these variables individually, although no study to date has provided support for this hypothesis in a statistically stringent fashion.…”
mentioning
confidence: 99%
“…First, the concept of outcome prediction in DLBCL patients using blood-based biomarkers such as neutrophil and lymphocyte counts, C-reactive protein, and albumin is not new [4]. Low serum albumin and low BMI are frequent findings in patients with advanced malignancy, and can be considered as proxy variables for poor performance status and cancer-associated cachexia/anorexia [4,5].…”
mentioning
confidence: 99%